Council House Movie Star: Que(e)rying the Costume. Issue 1 (1st October 2014) - Edward, Mark
Council House Movie Star (2012) originally started as a film enquiry exploring what happens when drag queens age, both off stage and onstage. The research expanded to include two further practice projects: an immersive gallery installation of a life-size council house and a fine art exhibition of the naked and costumed drag body. This article examines the quotidian experiences of a white working-class drag hero/ine and the costumed genderqueered skin. It discusses the queer costume of drag queens, including make-up and wigs. The article also explores the position of memory within the formation of costume for performance as a major theme within the creative processes and design of this project. This visual essay narrates the positioning of drag queens within the social realities of working-class life, thus producing an interesting contrast between the costume of chavs, B-boys and contemporary youth, against the queer and camp drag costume.